MELANCHOLY AND RESISTANCE: A POSTFEMINIST READING OF LANA DEL REY’S NORMAN FUCKING ROCKWELL! ALBUM - Puspitalia Permata Nurani; Vino Dwi Ananda (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2025)
This article explores Norman Fucking Rockwell!, the 2019 studio album by American singer-songwriter Lana Del Rey, as a postfeminist cultural text that navigates the intersections of femininity, melancholy, and resistance in contemporary popular culture. The research addresses how Del Rey’s lyrical persona performs and problematizes postfeminist sensibility through affective narratives of vulnerability, aesthetic detachment, romantic fatalism, and ironic self-awareness. Employing a postfeminist critical framework—drawing on theories by Rosalind Gill, Angela McRobbie, Judith Butler, Sara Ahmed, and Lauren Berlant—this study also incorporates insights from popular culture theorists such as John Fiske, Dominic Strinati, and John G. Cawelti to situate the album within broader traditions of formulaic storytelling and cultural semiotics. The analysis is conducted through close reading and intertextual interpretation of all fourteen tracks, examining lyrics, performance style, and affective cues. Each track is treated as a discrete narrative unit that contributes to a larger postfeminist discourse: from the ironic empowerment in Norman Fucking Rockwell to the quiet withdrawal in Bartender, and the melancholic resistance in hope is a dangerous thing for a woman like me to have – but I have it. The study reveals that Del Rey’s work simultaneously reflects and subverts postfeminist norms by embracing emotional opacity, stylized despair, and self-reflexive critique. Rather than offering straightforward narratives of empowerment, the album presents femininity as fractured, polysemic, and politically potent in its refusal to conform to coherent neoliberal scripts. Through its interplay of confession and critique, visibility and erasure, Norman Fucking Rockwell! constructs a melancholic femininity that challenges the commodified affect of the “empowered woman” archetype. This article concludes that Del Rey’s body of work does not merely reproduce postfeminist themes, but consciously manipulates them—transforming the album into a literary and cultural text where sadness becomes strategy, and vulnerability, a form of resistance. Keywords: Postfeminism, Melancholy, Popular music, Lana Del Rey, Gender performativity